PREPARASI KOMPOSIT KITOSAN-ALUMINA BEADS SEBAGAI ADSORBEN ION LOGAM KADMIUM(II) DAN NIKEL(II) DALAM LARUTAN - Noviana, Melly; Mahatmanti, F Widhi (Indonesian Journal of Chemical Science, 2020)
It has been done preparation of composite beads from chitosan and alumina for adsorption Cd(II) and Ni(II). Research includes the preparation of adsorbents (chitosan beads, alumina, and composite beads) and adsorption optimization including pH, contact time, concentration and selectivity. FT-IR characterization showed the presence of a typical group of composite beads. The SAA characterization showed chitosan beads including micropores, alumina and composite beads including mesopores. The optimization results of Cd(II) adsorption showed the optimum concentration at 0.55 mmol/L, while the optimization of pH and contact time of chitosan beads were obtained at pH 6 for 90 minutes, optimum alumina at pH 5 for 60 minutes, and optimum composite beads at pH 6 for 60 minutes . The optimization results of Ni(II) adsorption showed the optimum contact time at 60 minutes, while the optimization of pH and the concentration of chitosan beads occurred at pH 6 with a concentration of 0.65 mmol/L, optimum alumina at pH 7 with a concentration of 0.65 mmol/L, and the optimum composite beads at pH 6 with a concentration of 0.55 mmol/L. The amount of adsorbed Ni(II) 3,797x10-2 mmol/g and Cd(II) 1,7997x10-2 mmol/g, so that composite beads are more selectively adsorbing Ni(II) compared to Cd(II).